Case Report: Thrombotic-Thrombocytopenic Purpura Following Ipilimumab and Nivolumab Combination Immunotherapy for Metastatic Melanoma - Mullally, W. J.; Cooke, F. J.; Crosbie, I. M.; Kumar, S.; Abernethy, V. E.; Jordan, E. J.; O’Connor, M.; Horgan, A. M.; Landers, R.; Naidoo, J.; Calvert, P. M. (Frontiers in Immunology, 2022)
A man in his early 50s presented with small bowel obstruction, requiring emergency laparoscopic small bowel resection for the metastatic melanoma of the jejunum with no identifiable primary lesion. One week after his first treatment with ipilimumab and nivolumab, he presented with diffuse abdominal pain, constipation, and fatigue. A computerized tomography scan did not identify a cause for his symptoms. This was rapidly followed by thrombocytopenia on day 11 and then anemia. He commenced intravenous corticosteroids for a suspected diagnosis of immune-related thrombocytopenia. On day 15, a generalized onset motor seizure occurred, and despite plasmapheresis later that day, the patient died from fatal immune-related thrombotic thrombocytopenic purpura (TTP). This was confirmed with suppressed ADAMTS13 (<5%) testing on day 14. Immune-related TTP is a rare and, in this case, fatal immune- related adverse event. Further studies are required to identify additional immunosuppressive management for immune-related TTP.